Ngamuk dan Psikoterapi Mawas Diri Suryomentaram - Istiana Kuswardani (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2009)
This article was aimed to identify the “Mawas Diri Method in Suryometaraman” as alternative psychoterapy approach to reduce outraged behavior (Ngamuk) in Javanese community. In Javanese culture, Ngamuk perceived as a non-specific behavior which characterized with hostile, threatening and dangerous for others. Using content analysis, this reseach then identified that Ngamuk as a common behavior-self-control problem in Javanese people inherrited within as well as influenced by Javanese Culture. The basic asumpsions for this approach was: when the abnormalities come out from a cultural character, then the best way to reduce the occurance of the symptoms was the approach inherrited within the culture itself. The method proposed was Mawas Diri which has 4 steps in its approach: (1) Re-evaluating the “like-dislike” responses (2) Understanding oneself and empathizing the feeling of others (3) Taking actions with “here and now” perspectives (4) Generating the sense of adequateness in responding to life demand. The therapists willing to use this cultural approach to treat Javanese clients with outraged problems, need to take extra precautions regarding to their cultural value, identity and background as Javanese people due to excessive acculturation in Javenese Community.Keywords: ngamuk, javanese culture, mawas diri, suryomentaraman